KEWENANGAN KEMENTERIAN AGAMA DALAM PERIZINAN OPERASIONAL LEMBAGA PENDIDIKAN KEAGAMAAN DAN PONDOK PESANTREN DI KABUPATEN ACEH BESAR - Azzahri, M.Saleh Sjafei, Mujibussalim. (Jurnal Ilmu Hukum, 2014)
Abstract: The mechanism of the issuance of religious educational institutions and Islamic boarding school by the Ministry of Religion is done by earlier consulting between leaders or managers of religious educational institution and Islamic boarding school, then followed by the application by fulfilling general and specific conditions depending on the institution offered and fulfilling other juridical requirements including recommendations from regional government issued by the Department of Welfare, Development, Protection of Society in Aceh Besar District and Aceh Province. Moreover, the application is going to be processed by the Ministry of Religion of Aceh Besar and if by the research and survey conducted by the Ministry of Religion of Religious Educational Institution and Islamic boarding school which have fulfilled conditions then it will be issued by the Ministry. The license then becoming main condition in the educational institutions and the schools obtaining several forms of aids from government (central or regional) or the third party in conducting its operational. The obstacles faced by the Ministry in issuing the license of religious education and Islamic boarding school in Aceh Besar consists of two that are the internal constraint relating to existing laws, difficulty in identifying the need and interest of society quickly because the width of area of Aceh Besar District and the lack of human resource in the Ministry of Religion Aceh Besar. Apart from that, the District of Aceh Besar is facing the external obstacles comprising a lack of law awareness of society and the managers of the institution and the school to get the license needed to run the institutions and the school, lack of coordination with other related institutions and there is no good law enforcement on the management of religion education and the school that is not obeying the existing laws Keywords : Religion Ministry, Religious Education Institutions and Islamic Boarding School. Abstrak: Mekanisme penerbitan izin operasional lembaga pendidikan keagamaan dan pondok pesantren oleh Kantor Kementerian Agama di Aceh Besar didahului adanya konsultasi antara pimpinan atau pengelola lembaga pendidikan keagamaan dan pondok pesantren, kemudian pengajuan permohonan dengan melengkapi persyaratan umum dan persyaratan khusus tergantung jenis lembaga yang diajukan serta memenuhi persyaratan yuridis lainnya, termasuk dalam hal ini adanya rekomendasi dari pemerintah daerah yang dikeluarkan oleh Kesbanglinmas Kabupaten Aceh Besar dan Provinsi Aceh. Selanjutnya permohonan kemudian akan diproses oleh pihak Kementerian Agama Kabupaten Aceh Besar dan apabila melalui penelitian dan survey yang dilakukan oleh Kementrian Agama lembaga pendidikan keagamaan dan pondok pesantren yang bersangkutan memenuhi syarat maka akan diterbitkan izin dimaksud oleh Menteri Agama. Izin Kementerian Agama ini kemudian juga menjadi persyaratan utama dalam hal lembaga pendidikan keagamaan dan pondok pesantren memperoleh berbagai bentuk bantuan dari pemerintah (APBN/APBD) maupun pihak ketiga dalam menjalankan operasionalnya. Kendala yang dihadapi dalam penerbitan izin, yaitu kendala internal yang menyangkut ketentuan perundang-undangan yang berlaku, sulitnya melakukan identifikasi kebutuhan dan kepentingan aspirasi masyarakat secara cepat karena luasnya wilayah Kabupaten Aceh Besar dan adanya keterbatasan sumber daya di dalam Kementerian Agama Kabupaten Aceh Besar sedangkan kendala eksternal yang meliputi masih lemahnya kesadaran hukum masyarakat dan pengelola lembaga pendidikan keagamaan dan pondok pesantren untuk mengurus perizinan yang diperlukan untuk penyelenggaraan lembaga pendidikan keagamaan dan pondok pesantren, lemahnya koordinasi dengan instansi terkait lainnya dan belum adanya penegakan hukum yang tegas terhadap pengelola lembaga pendidikan keagamaan dan pondok pesantren yang tidak mematuhi ketentuan yang berlaku. Kata kunci : Kementerian Agama, Lembaga Pendidikan Keagamaan dan Pondok Pesantren.